Analysis of the Impact of the Qaliwarma Program on the Academic Performance of Students in Primary Schools in San Roman Province, Puno, Peru - Ticona-Carrizales, Lucio; Rodríguez-Limachi, Omar Moisés; Incacutipa-Limachi, Duverly Joao; Rodríguez-Chokewanca, Ingrid Rossana; Campos-Segales, Betty; Arpasi-Lima, Wilson Smith (Journal of Ecohumanism, 2024)
The research work had the general objective of analyzing the impact of the Qali Warma Program on the quality of life of students in primary educational institutions in the province of San Roman, the quantitative approach of non-experimental design was used, the study population and sample consisted of 80 parents of primary educational institutions in the province of San Roman, the results revealed that the satisfaction of students with the food provided by the program is neutral, with 56. 25% of parents perceiving it this way, 33.75% not very satisfied and only 10% very satisfied, likewise there is an increase in the number of approved students making a difference of 1336 students between the periods 2016 - 2023, and a reduction of disapproved students of 84, as a final conclusion it was determined that the Qali Warma Program has a moderate impact on the quality of life and academic performance of primary students in San Roman, with a majority of parents who perceive the program in a neutral way. However, the program has demonstrated success in improving academic performance and increasing the number of beneficiaries, contributing to the development of skills and progress in reading comprehension and mathematics.Feeding